2021
DOI: 10.1002/mbo3.1201
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial and fungal community composition in time and space in the nest mounds of the ant Formicaexsecta (Hymenoptera: Formicidae)

Abstract: In a subarctic climate, the seasonal shifts in temperature, precipitation, and plant cover drive the temporal changes in the microbial communities in the topsoil, forcing soil microbes to adapt or decline. Many organisms, such as mound‐building ants, survive the cold winter owing to the favorable microclimate in their nest mounds. We have previously shown that the microbial communities in the nest of the ant Formica exsecta are significantly different from those in the surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 112 publications
(126 reference statements)
2
17
0
Order By: Relevance
“…These results show that Formica exsecta exhibits a distinct microbial community both within the body (this study), and in the surrounding environmental matrix that constitutes their nest mound (this study and Lindström et al, 2021). These taxonomically distinct communities are constantly in contact with each other, given that the ants continuously handle nest material, transfer cuticular microbiota via social grooming and hygiene behaviours, and exchange crop contents with microbiota therein (Cremer et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These results show that Formica exsecta exhibits a distinct microbial community both within the body (this study), and in the surrounding environmental matrix that constitutes their nest mound (this study and Lindström et al, 2021). These taxonomically distinct communities are constantly in contact with each other, given that the ants continuously handle nest material, transfer cuticular microbiota via social grooming and hygiene behaviours, and exchange crop contents with microbiota therein (Cremer et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…Based on the outcome from our earlier studies (Lindström et al, 2019;Lindström et al, 2021) we hypothesize that the ants inhabiting the nest may have a core microbiome that significantly differs in community composition and/or community structure from that of the nest material, yet may show variation among colonies. The core microbiome of the ants would in this case be characterized by signature microbes, sensu Shade and Handelsman (Shade & Handelsman, 2012) that are absent or rare in the nest material, but are consistently present and significantly more abundant in the ants.…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and 4 ) showed that mounds and shallow soils had overlapping microbial composition, indicating that the microbial communities of these sample categories differed in relative abundance rather than in microbial composition. Interestingly, previous studies on microbial communities in nests of mound-building ants demonstrated that bacteria and fungal communities of the nest differed significantly from those of the surrounding soils with respect to both community structure and taxonomic composition ( Lindström, Timonen & Sundström, 2021 ; Lindström et al, 2019 ). It is possible that the differences in relative abundance between microbial communities of scrubfowl mounds and surrounding soils are related to the increased temperatures resulting from microbial metabolic activity in the mound.…”
Section: Discussionmentioning
confidence: 94%
“…The level of genetic diversity within colonies is therefore expected to be associated with the diversity of pathogens that colonies naturally face. Microbial analyses identified a wide range of pathogens from ants and within ant nests, including soil bacterial and fungal parasites (Johanson et al 2013;Luccas et al 2017;Lindström et al 2021). Although the diversity of pathogens potentially infecting Cataglyphis colonies remains unknown, one may suppose that exposition to a large suite of microbes is common since workers forage for and bring back dead insects to the nests (Bocher et al 2007).…”
Section: Discussionmentioning
confidence: 99%